The salt to my soap / Nadia Liana Mohd Karim and Putri Dahlia Ab Rashid - Mohd Karim, Nadia Liana; Ab Rashid, Putri Dahlia (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Living in Malaysia we are blessed with arrays of coastline. As the sun shines throughout the year, some people even make it a way of life to be by the beach at very regular intervals. Malaysians generally enjoy having picnics by the beach and swimming in the sea; thus, washing up is regularly perform following the said activities. Cleansing however is far from effective when it comes to sea water. The easiest example of hard water is any water that is not treated. It contains significant amount of mineral such as calcium, magnesium, sulphates and sometimes copper, making it difficult for conventional soaps to foam - and foam is the agent that takes away impurities. On top of that, foam also plays a role in psychological effect that influence one's satisfaction or feeling of completeness when cleansing.